Zebrafish as a New Tool in Heart Preservation Research - Luciana Da Silveira Cavalcante; Shannon N. Tessier (Journal of Cardiovascular Development and Disease, 2021)
Heart transplantation became a reality at the end of the 1960s as a life-saving option for patients with end-stage heart failure. Static cold storage (SCS) at 4–6 °C has remained the standard for heart preservation for decades. However, SCS only allows for short-term storage that precludes optimal matching programs, requires emergency surgeries, and results in the unnecessary discard of organs. Among the alternatives seeking to extend ex vivo lifespan and mitigate the shortage of organs are sub-zero or machine perfusion modalities. Sub-zero approaches aim to prolong cold ischemia tolerance by deepening metabolic stasis, while machine perfusion aims to support metabolism through the continuous delivery of oxygen and nutrients. Each of these approaches hold promise; however, complex barriers must be overcome before their potential can be fully realized. We suggest that one barrier facing all experimental efforts to extend ex vivo lifespan are limited research tools. Mammalian models are usually the first choice due to translational aspects, yet experimentation can be restricted by expertise, time, and resources. Instead, there are instances when smaller vertebrate models, like the zebrafish, could fill critical experimental gaps in the field. Taken together, this review provides a summary of the current gold standard for heart preservation as well as new technologies in ex vivo lifespan extension. Furthermore, we describe how existing tools in zebrafish research, including isolated organ, cell specific and functional assays, as well as molecular tools, could complement and elevate heart preservation research.